How Many Screws to Use: A Report of Outcomes After Surgical Stabilization of Rib Fractures Where less than the Manufacturer Recommended Screw Number Were Applied. Issue 5 (May 2022) - Nowack, Timothy; Christie, Dudley; Nonnemacher, Cory; Buchanan, John
Surgical stabilization of rib fractures in an effective technique for the management of bony thoracic trauma. However, rib fractures location or morphology may make the placement of the recommended 6 screws impossible. A retrospective analysis of patients receiving SSRF at our facility from 2009–2019 identified cases where less than the recommended screw placement was used. Respiratory complications and hardware integrity were analyzed using follow-up imaging and examinations when available. A total of 62 patients were identified that used less than the recommended number of screws. The majority of these were in the lateral and posterior chest wall positions. 1 pleural effusion, no pneumothoraces, deaths, or hardware dislodgments were identified. While the authors do not advocate for the routine deviation from manufacture recommendations, we concluded that in select circumstances, adequate fixation can be achieved with less than 6 screws across a plated fracture.